MENINGKATKAN KESADARAN CYBER SECURITY DI SEKTOR PERBANKAN - Hidayat, Rahmat Rian; Kahfi, Arbi Abdul; Sulomo, Agus; Amaliah, Naima (Jurnal Pengabdian Masyarakat Nasional, 2023)
As information becomes increasingly important in companies, information threats and vulnerabilities also increase, as evidenced by the emergence of certain hacks/information leaks that impact organizations. Information security awareness is important to any organization's efforts to safeguard information. All organizational efforts to safeguard information may become ineffective due to such risks. Therefore, awareness is the starting point for all personnel in a company to pursue or understand knowledge about cyber security. With security awareness, an employee can focus his or her attention on one or more potential problems or dangers. So, to create awareness among the public or bank employees, one way is to deliver material, through Community Service events with the theme of cyber security. This activity was carried out online using zoom media which was attended by 524 participants and consisted of several lecturers as resource persons who used educational and evaluation methods in delivering the material. Based on the activities that have been carried out and the evaluation results during this community service activity, we can conclude that the community service program has been able to provide benefits for participants in this training, especially in building awareness of information security in the banking environment. Participants were able to understand well based on the evaluation results which showed that 93% of participants were able to answer questions with scores that passed the standard